Analysis of Fishermen's Responses as an Effort to Mitigate And Adapt to Climate Change in Tambak Lorok - Rahmawati, Nadhea Oktaviantina; Wiryawan, Adam (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
Climate change is a natural phenomenon resulting from global warming on earth which occurs continuously and increases every year. The main factor causing global warming is greenhouse gases produced from human and industrial activities. Coastal areas are zones that play a large role in the world carbon cycle which influences global warming. The low response of coastal communities to climate change can have an impact on the emergence of social and ecological problems, namely tidal floods. Social and ecological issue in coastal areas are important things that are tied to each other. The research purpose is to analyze the fishermen’s response to climate change as a mitigation and adaptation effort in Tambak Lorok, Semarang City. This research uses a mixed methode approach, with research subjects of 35 respondents. The research results show that as many as 67.72% of the fisherman’s already respond to the climate change phenomenon in Tambak Lorok, Semarang City. The climate change mitigation efforts carried out are mangrove restoration and conservation by cultivating mangroves and collaborating with Corporate Social Responsibility to carry out environmental programs based on mangrove conservation such as the planting program of 1000 mangroves in the coastal area of Tambak Lorok. It is hoped that this program can be a commitment of the community and industry that synergize to mitigate climate change in Tambak Lorok.